2011
DOI: 10.1075/idj.19.1.04cha
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the legibility of isolated characters of onscreen typefaces

Abstract: This study reports on the legibility of digits, symbols, and letters from 20 onscreen typefaces. Participants were asked to identify individual characters after a brief exposure and performance was recorded. Classification tree analysis was used to examine the influence of specific character features on legibility. Features included attributes such as height, width, weight, stroke variation, contrast, and complexity. Results reveal the most influential features for six commonly confused characters (zero, one, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Some studies showed how font design features could affect the legibility of specific characters. One of the recent researches [10] examined the legibility of isolated letters, individual digits, and symbols of 20 onscreen typefaces. Experiment have been conducted on ten subjects completing 188 trials in which the characters were exposed in a single presentation for 34 milliseconds, and subjects were asked to name them aloud.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed how font design features could affect the legibility of specific characters. One of the recent researches [10] examined the legibility of isolated letters, individual digits, and symbols of 20 onscreen typefaces. Experiment have been conducted on ten subjects completing 188 trials in which the characters were exposed in a single presentation for 34 milliseconds, and subjects were asked to name them aloud.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the proportion between the word height WH and descender has been calculated as in (9) using letter 'Meem' ‫. )م(‬ The ratio among three measurements, tooth/loop height, ascender and descender, have been calculated using equations (10)…”
Section: Measuring Font Design Featuresmentioning
confidence: 99%